The Relationship Between Attachment Styles, Emotional Intelligence, and Self-esteem in Only-child Families and Two-children Families - Rahmani, Noora (2021)
Emotional intelligence, attachment style, and self-esteem are important variables in social interaction that can affect the social relationship. Also having one child is an important issue in which parents are worried about it which is the adolescent's single families have weaknesses in social relationships and interaction? In this study, the researcher tries to investigate the relationship between emotional intelligence, attachment style, and self-esteem in single-child and two-children adolescents aged range 13-17 (male and female). The current research used a quantitative survey study and used three questionnaires; inventory of parent and peer attachment (IPPA), inventory of trait emotional intelligence questionnaire (TEIQue), self-esteem inventory (TSI), and the socio-demographic form developed by the researcher. The participant was 228 adolescents 13-17 years old (male and female). And for the relationship between the three variables the researcher used regression and correlation and used t-test and ANOVA for comparison of socio-demographic (only or two children, gender, and age) with these variables. The result of this study showed that there is a significant relationship between emotional intelligence and self-esteem. Also, there were no significant differences between single-child and two-children in emotional intelligence, attachment style, and self-esteem. In differences of gender (girl and boy), there was a statistically significant in self-esteem and emotional intelligence between girls and boys but not in an attachment. Also in age, there were statistically significant differences in attachment between 13 and 16. Parents, therapists, and adolescent counselors should be aware of the importance of emotional intelligence and self-esteem and they should be careful about the single-child and their abilities.